2002
DOI: 10.1590/s0100-41582002000600010
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento da população de Phytophthora infestans na região da Zona da Mata de Minas Gerais de 1998 a 2000

Abstract: Foram caracterizados 212 isolados de Phytophthora infestans obtidos de 51 lavouras de tomate (Lycopersicon esculentum)e batata (Solanum tuberosum), em sete municípios da Zona da Mata, MG. Todos os isolados tiveram o grupo de compatibilidade determinado; 96 isolados foram caracterizados para a isoenzima glucose 6-fosfato-isomerase (Gpi); 71 isolados foram analisados quanto à resistência ao metalaxyl; e determinou-se o espectro de virulência de 46 isolados. Todos os 212 isolados testados foram classificados como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Due to the host specificity of clonal lineages of P. infestans in Brazil, only isolates of the mating type A1 have been found associated with tomato plants. Isolates of the mating type A2 (BR-1 clonal lineage), and only sporadically A1, are associated with potato plants (Reis et al, 2002(Reis et al, , 2003. As only isolates of the mating type A1 remain associated with tomato plants, there is no risk at all or low risk of sexual reproduction of P. infestans on this host.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the host specificity of clonal lineages of P. infestans in Brazil, only isolates of the mating type A1 have been found associated with tomato plants. Isolates of the mating type A2 (BR-1 clonal lineage), and only sporadically A1, are associated with potato plants (Reis et al, 2002(Reis et al, , 2003. As only isolates of the mating type A1 remain associated with tomato plants, there is no risk at all or low risk of sexual reproduction of P. infestans on this host.…”
Section: Resultsmentioning
confidence: 99%
“…Its isolates have the A1 mating type, and the restriction pattern of mitochondrial DNA (mtDNA) is of the Ib type. The new lineage, BR-1, is associated with potato crops, and its isolates have the A2 mating type, and mtDNA IIa (Reis et al, 2002(Reis et al, , 2003. The host specificity of clonal lineages is, at least in part, due to quantitave differences in aggressiveness components (Suassuna et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates of this lineage have the A1 mating type with Ib type restriction pattern of mitochondrial DNA (mtDNA). The other lineage, having A2 mating type with mtDNA IIa BR-1, was found to be linked with potato crops (Reis et al, 2002(Reis et al, , 2003) [74,75] . The presence of quantitative differences in the components of aggresivity in the clonal lineages contributed to the specificity of host (Suassuna et al, 2004) [89] .…”
Section: Cause Of Development Of Metalaxyl Resistancementioning
confidence: 99%
“…However from the subsequent analysis of oospore progeny, it was observed that metalaxyl resistance and fitness were not linked (Gisi and Cohen, 1996). In Brazil, the P. infestans population from tomatoes showed uniformity (Reis et al, 2002) [75] , as recombination and migration does not occur within pathogenic population, the prime reason of variability may be mutation. Though, P. infestans population in Brazil has apparent genetic uniformity, mutation is the expected factor which can affect the management of disease, like insensitivity to fungicides and variability in virulence.…”
Section: Cause Of Development Of Metalaxyl Resistancementioning
confidence: 99%